Rising from the muck : the new anti-semitism in Europe - Taguieff, Pierre-André 1946- (Ivan R. Dee, 2004)
"Never since the close of World War II have anti-Jewish sentiments gained such currency in France among so many different social groups. Never have these sentiments been so publicly expressed and met so little intellectual and political resistance as they have since the year 2000. As the number of anti-Jewish incidents escalates, the anti-racist demonstrations that ordinarily would respond to them are nowhere in sight." "In Rising from the Muck, Pierre-Andre Taguieff raises questions about this shockingly common acceptance of anti-Semitic attitudes and behavior. He surveys the landscape of contemporary anti-Semitism from his position on the scene, describing its leading figures and the role played by the conflict between Israelis and Palestinians. He analyzes in detail the Islamist influence in promoting anti-Zionism, and the blindess, complacency, or complicity of various French institutions, groups, and individuals." "The new wave of anti-Semitism spreading around the world, Mr. Taguieff shows, is based on a polemical and fanciful amalgam of Jews, Israelis, and "Zionists" as representatives of an evil power. In the eyes of the new anti-Jews, the world's ills can be explained by Israel's existence. The chief occupation, purveyed especially by international Islamist circles and the heirs to Third Worldism, is that "Zionism," far from being a respectable nationalism like that of the Palestinians, is actually a form of colonialism, imperialism, and racism. The old European anti-Semitism, the author notes, was a particular kind of racism, directed against Jews. The new worldwide anti-Semitism seeks to turn the charge of racism against the Jews."--BOOK JACKET.